A cross-sectional study on prevalence of obesity and its association with dietary habits among college students in Abha, Saudi Arabia - Alshahrani, Mana M.; Chandramohan, Sriram (International Journal Of Community Medicine And Public Health, 2017)
Background: During the past few years there was a western influence in the kingdom of Saudi Arabia and as a result of it the eating habits among the male college students had rapidly changed which also increased the prevalence rate of overweight and obesity. Therefore the objectives of the study were 1) To determine the prevalence of overweight and obesity in a sample of male college students in Abha, Saudi Arabia. 2) To determine the relationship between the Student’s body weight and their eating habits. Methods: A cross-Sectional study was done among 445 male college students from king Khalid University, Abha Saudi Arabia. Study participants were selected randomly and self-administered questionnaire was used to collect the data. Data was analyzed by using the statistical package for social sciences (SPSS Inc. version 16.) and expressed in percentages. Results: The study found that 28% and 20 % of students were overweight and obese. Daily intake of snacks and lack of consumption of vegetable and fruits were found to be the common dietary habits among the male college students. Majority of the students were aware about the balanced nutrition and it was positively correlated with the normal body weight. Conclusions: The current study suggest involvement of college Administration and family members will further reduce the burden of overweight and obesity among college students in the nation.